2022
DOI: 10.3389/fcvm.2022.828556
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Simulation of Left Ventricular Hemodynamics: A Pilot Study in Mitral Regurgitation and Left Ventricle Aneurysm Patients

Abstract: BackgroundCardiac CT (CCT) is well suited for a detailed analysis of heart structures due to its high spatial resolution, but in contrast to MRI and echocardiography, CCT does not allow an assessment of intracardiac flow. Computational fluid dynamics (CFD) can complement this shortcoming. It enables the computation of hemodynamics at a high spatio-temporal resolution based on medical images. The aim of this proposed study is to establish a CCT-based CFD methodology for the analysis of left ventricle (LV) hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 69 publications
2
37
0
Order By: Relevance
“…To retrieve reasonable initial conditions, two cycles were computed in advance. As results in a previous study suggested, a sufficiently swung-in state can be assumed after two cycles for such dilated LVs with reduced EF ( 29 ). In the same study, mesh convergence was shown for the specified mesh dimensions.…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…To retrieve reasonable initial conditions, two cycles were computed in advance. As results in a previous study suggested, a sufficiently swung-in state can be assumed after two cycles for such dilated LVs with reduced EF ( 29 ). In the same study, mesh convergence was shown for the specified mesh dimensions.…”
Section: Methodsmentioning
confidence: 90%
“…The mean shapes of all seven subcohorts are used to set up the simulation. A detailed description of the workflow can be found in our recently published work ( 29 ). Average shapes are computed for the cardioid mitral annulus and the elliptical aortic annulus which are used to reconstruct the entire LVEDV via a Poisson Surface Reconstruction algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations